Three-Dimensional Finite Element Analysis of the Pile Foundation Behavior in Unsaturated Expansive Soil - Wu, Xingyi (Université d'Ottawa / University of Ottawa, 2021)
Expansive soils, which are widely referred to as problematic soils are extensively found in many countries of the world, especially in semi-arid and arid regions. Several billions of dollars are spent annually for maintenance or for repairs to the structures constructed with and within expansive soils. The major problems of expansive soils can be attributed to the volume changes associated with the alternate wetting and drying conditions due to the influence of environmental factors. Pile foundations have been widely accepted by practicing engineers as a reasonably good solution to reduce the damages to the structures constructed on expansive soils. Typically, piles foundations are extended through the active layer of expansive soil to reach the bedrock or placed on a soil-bearing stratum of good quality. Such a design and construction approach typically facilitates pile foundations to safely carry the loads from the superstructures and reduce the settlement. However, in many scenarios, damages associated with the pile foundations are due to the expansion of the soil that is predominantly in the active zone that contributes to the pile uplift. Such a behavior can be attributed to the water infiltration into the expansive soil, which is a key factor that is associated with the soil swelling. Due to this phenomenon, expansive soil typically moves upward with respect to the pile. This generates extra positive friction on the pile because of the relative deformation. If the superstructure is light or the applied normal stress on the head of the piles is not significant, it is likely that there will be an uplift of the pile contributing to the damage of the superstructure. In conventional engineering practice, the traditional design methods that include the rigid pile method and the elastic pile method are the most acceptable in pile foundation design. These methods are typically based on a computational technique that uses simplified assumptions with respect to soil and water content profile and the stiffness and shear strength properties. In other words, the traditional design method has limitations, as they do not take account of the complex hydromechanical behavior of the in-situ expansive soils. With the recent developments, it is possible to alleviate these limitations by using numerical modeling techniques such as finite element methods. In this thesis, a three-dimensional finite element method was used to study the hydro-mechanical behavior of a single pile in expansive soils during the infiltration process. In this thesis, a coupled hydro-mechanical model for the unsaturated expansive soil is implemented into Abaqus software for analysis of the behavior of single piles in expansive soils during water infiltration. A rigorous continuum mechanics based approach in terms of two independent stress state variables; namely, net normal stress and suction are used to form two three-dimensional constitutive surfaces for describing the changes in the void ratio and water content of unsaturated expansive soils. The elasticity parameters for soil structure and water content in unsaturated soil were obtained by differentiating the mathematical equations of constitutive surfaces. The seepage and stress-deformation of expansive soil are described by the coupled hydro-mechanical model and the Darcy’s law. To develop the subroutines, the coupled hydro-mechanical model is transferred into the coupled thermal-mechanical model. Five user-material subroutines are used in this program. The user-defined field subroutine (USDFILD) in Abaqus is used to change and transfer parameters. Three subroutines including user-defined material subroutine (UMAT), user-defined thermal material subroutine (UMATHT), and user-defined thermal expansion subroutine (UEXPAN) are developed and used to calculate the stress-deformation, the hydraulic behavior, and the expansion strain, respectively. Except for the coupled hydro-mechanical model of unsaturated expansive soils, a soil-structure interface model is implemented into the user-defined friction behavior subroutine (FRIC) to calculate the friction between soil and pile. The program is verified by using an experimental study on a single pile in Regina clay. The results show that for the single pile in expansive soil under a vertical load, water infiltration can cause a reduction in the pile shaft friction. More pile head load is transferred to the pile at greater depth, which increases the pile head settlement and pile base resistance. In future, the proposed method can also be extended for verification of other case studies from the literature. In addition, complex scenarios can be investigated to understand the behavior of piles in expansive soils.
Keywords: Expansive soil; Pile foundation; Coupled hydro-mechanical analysis; Coupled thermo-mechanical analysis